Effects of Irrational Parenthood Cognition, Family Support, and Resilience on Depression of Infertile Women - Eun Young Cho; Mi Hae Sung (Korean Society of Women Health Nursing, 2019)
PURPOSE: To determine effects of irrational parenthood cognition, family support, and resilience on depression in infertile women. METHODS: Subjects were 118 infertile women who agreed to participate in this study. Data were collected from April 16 to July 31, 2018. Collected data were analyzed using descriptive statistics, t-test, analysis of variance (ANOVA), Pearson's correlation and multiple regression with SPSS WIN 23.0 program. RESULTS: Depression significantly differed according to the burden of treatment cost and presence of people giving stress. Depression showed significantly positive correlation with irrational parenthood cognition and significantly negative correlations with family support and resilience. Factors affecting depression were irrational parenthood cognition, family support, and resilience. Irrational parenthood cognition had the greatest effect on depression. These three variables explained 35.8% of total variance. CONCLUSION: Irrational parenthood cognition, family support, and resilience affected depression of infertile women, with irrational parenthood cognition having the greatest effect. Therefore, it is important to develop and implement programs that can reduce irrational parenthood cognition and increase family support and resilience in order to lower depression of infertile women. The authors declared no conflict of interest.